LEGAL PROTECTION FOR HEALTH WORKERS AFTER THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS (RME) - Edisa Putra Ginting; Yasmirah Mandasari Saragih; Sumarno (PT. Sinergi Legal Publisher, 2024)
The development of information technology in the health sector has facilitated the use of Electronic Medical Records (EMR), which is regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022. EMR is intended to improve efficiency, accuracy, and security in patient data management. However, this transition also presents legal challenges, especially related to legal protection for health workers. This study aims to analyze the impact of the implementation of EMR on the legal protection of health workers, identify problems that arise, and propose policy recommendations. The method used is normative juridical with an analysis of related regulations and literature studies related to health data management practices. The results of the study indicate that although EMR provides various advantages in health data management, there are still shortcomings in implementation that can pose legal risks to health workers. Based on these findings, this study recommends increasing training and resources for health workers, as well as adjusting the technology infrastructure in health facilities to ensure compliance with the security and privacy standards set by the regulations. These recommendations are expected to support the effectiveness of the implementation of EMR and provide better legal protection for health workers.